corporate governance and financial performance of deposit taking SACCOs in Meru county - tharamba, eva kanini (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Corporate governance is a critical tool for enhancing the performance of Deposit-taking Savings and Credit Cooperative Societies (SACCOs) and ensuring they meet their members' economic and social needs. Properly structured cooperatives can contribute to equitable development and justice. However, a significant challenge facing these SACCOs is the issue of corporate governance. Some have faced mismanagement problems, resulting in the cessation of their operations. This study aimed to establish the relationship between corporate governance and financial performance of Deposit-taking SACCOs in Meru County, focusing on the impact of transparency. In addition, the study found that these SACCOs had effectively managed their liquidity, retaining funds for reinvestment rather than distributing all profits as dividends. The implications of these findings are substantial, particularly for the directors of Deposit-taking SACCOs and other cooperative organizations. They can use these insights to enhance governance practices within their societies, ultimately improving their overall performance. The study involved 92 directors from all eleven deposit taking SACCOs in Meru County, with a sample of 75 directors selected using stratified random sampling with proportional allocation. The questionnaire's reliability was validated through a pilot study. Data collection employed questionnaires containing close-ended questions and secondary data collected from the SACCO supervision annual report, the analysis encompassed descriptive and inferential statistics, including multiple regression analysis using SPSS software (Version 29). The results were presented in tables, highlighting the significant associations discovered between transparency, and the performance of Deposit-taking SACCOs in Meru County. Correlation and multiple regression analysis were conducted to establish between the study variable. The findings disclosed a significant association between transparency and financial performance of Deposit Taking SACCOs. The study recommends that Deposit-Taking SACCOs should engage with their customers frequently to keep them informed of the SACCO's progress and involve them in governance through voting rights in board decisions. These recommendations can contribute to better governance and improved SACCO financial performance. FROM: EVA THARAMBA